Вплив маркетингових, фінансових та цифрових технологій на розвиток інфокомунікаційної сфери як складової інноваційної інфраструктури - Гуцалюк, О.М.; Гаврилова, Н.В. (Вісник економічної науки України, 2020)
У статті розглянуті основні складові інфокомунікаційної сфери. Розкрито сутність маркетингових, фінансових та цифрових технологій та їх вплив на розвиток інфокомунікаційної сфери. Проаналізовано фінансову, маркетингову та цифрову складову розвитку інформаційної комунікації. Визначено необхідність розвитку інфокомунікаційної сфери для учасників: органів державної влади, бізнес-структур, населення. Запропоновано перспективи інфокомунікаційних технологій як складової інноваційної інфраструктури. Досліджено цілісну систему інфокомунікаційної сфери як складової інноваційної інфраструктури, розглянуто процес взаємодії учасників інфокомунікаційної сфери, проаналізовано витрати Державного бюджету на інфокомунікаційну сферу. Значну увагу в роботі приділено перспективам та очікуваній користі від впровадження маркетингових, фінансових та цифрових технологій для інфокомунікаційної сфери. У науковій праці запропоновано переваги розвитку інфокомунікаційної сфери для учасників. Для бізнесу це соціальні внески співробітників, корпоративний податок, ПДВ, реєстрація нової компанії, подання статистичної інформації, митні декларації, екологічні дозволи, держзакупівлі. Для громадян перелік більш розширений – ПДФО, пошук роботи, соціальні привілеї, особисті документи, реєстрація авто, громадські бібліотеки, заява в міліцію, заявка на дозвіл будівництва, свідоцтва на шлюб та народження, заявки на вступ до ЗВО, зміна адреси, сервіси охорони здоров’я. Запропоновані заходи подальшого розвитку інформаційного суспільства в Україні. В статье рассмотрены основные составляющие инфокоммуникационной сферы. Раскрыта сущность маркетинговых, финансовых и цифровых технологий и их влияние на развитие инфокоммуникационной сферы. Проанализированы финансовые, маркетинговые и цифровые составляющие развития информационной коммуникации. Определена необходимость развития инфокоммуникационной сферы для участников: органов государственной власти, бизнес-структур, населения. Предложены перспективы инфокоммуникационных технологий как составляющей инновационной инфраструктуры. Исследована целостная система инфокоммуникационной сферы как составляющей инновационной инфраструктуры, рассмотрен процесс взаимодействия участников инфокоммуникационной сферы, проанализированы расходы Государственного бюджета на инфокоммуникационные сферу. Значительное внимание в работе уделено перспективам и ожидаемой пользе от внедрения маркетинговых, финансовых и цифровых технологий для инфокоммуникационной сферы. В научной работе предложены преимущества развития инфокоммуникационной сферы для участников. Для бизнеса это социальные взносы сотрудников, корпоративный налог, НДС, регистрация новой компании, представление статистической информации, таможенные декларации, экологические разрешения, госзакупки. Для граждан перечень более расширенный – НДФЛ, поиск работы, социальные привилегии, личные документы, регистрация авто, общественные библиотеки, заявление в милицию, заявка на разрешение строительства, свидетельства на брак и рождение, заявки на вступление в ЗВО, изменение адреса, сервисы здравоохранения. Предложенные меры дальнейшего развития информационного общества в Украине. The purpose of the article is to consider and analyze marketing, financial and digital technologies that influence the development of the infocommunication sphere as a component of the innovation infrastructure. The main components of the infocommunication sphere are considered in the article. The essence of marketing, financial and digital technologies and their influence on the development of infocommunication sphere is revealed. The financial, marketing and digital components of information communication development are analyzed. The necessity of development of infocommunication sphere for participants is considered: public authorities, business structures, population. Prospects of infocommunication technologies as a component of innovation infrastructure are considered. The scientific article considers the integral system of the infocommunication sphere as a component of the innovation infrastructure, considers the process of interaction of the participants of the infocommunication sphere, analyzes the expenditures of the State budget for the infocommunication sphere. Considerable attention is paid to the prospects and expected benefits of the introduction of marketing, financial and digital technologies for the infocommunication sphere. The advantages of development of infocommunication sphere for participants are considered in the work. For business, these are social contributions of employees, corporate tax, VAT, registration of a new company, submission of statistical information, customs declarations, environmental permits, public procurement. For citizens, the list is more extended, job search, social benefits, personal documents, car registration, public libraries, application to the police, application for a building permit, marriage and birth certificates, applications for university admission, change of address, health services 'I. Measures for further development of the information society in Ukraine are considered. Thus, the identified strategic objectives of creating a modern innovation system, which will include technology and science parks, venture funds, technology transfer networks, etc., requires the introduction of public-private (public-private) partnerships in the innovation sphere and should be aimed at legislatively establishing incentives for new industries, as well as companies in the field of infocommunications.